Analisis Penilaian Risiko Pengembangan Aplikasi GA Service Menggunakan Failure Mode and Effect Analysis (FMEA) – Studi Kasus Perusahaan Jasa PT XYZ - Sofianingtias, Aisyah; Prasetya, Machmudin Eka (Owner : Riset dan Jurnal Akuntansi, 2024)
Along with technological developments, a derivative form of corporate digital transformation of the General and Property Assets Division (DIV MUM) of PT XYZ Head Office is developing in the form of a digital transformation general affairs application program. The existence of digital transformation is not only able to reduce operational costs and increase productivity but also able to strengthen competitiveness between companies and overall performance. This research is interesting to study because with the new system, in addition to the risks that need to be mapped first, this application can be a cost reduction for the company. This research uses qualitative analysis, with data collection techniques in this research using mixed methods. The unit of analysis used, namely the data analysis unit, is a single unit with a single case study. The risk mapping results state that there are three risks that fall into the "extreme" category, nine risks fall into the "high" category, five risks fall into the "medium" category, and eleven risks fall into the "very low" category. Then the mapping results can determine the priority risks of the GA Service application development process, there are 17 risks.